Armed Conflict in Karen Area in the Era of Myanmar 2021 Military Coup - Lwin, Kyaw (Advanced Studies on Socio-Economy Development, 2025)
Although the revolution has been going on for more than 70 years, the Myanmar military and allies are fighting the KNU and its allies' attitudes, behaviors, and contradictions under Saw Ba U Gyi's four guiding principles of the revolution using the excuse of fighting for autonomy and secession of armed organizations from the Union. Peace talks with the State Law and Order Restoration Council in 1994 failed. Peace talks and a nationwide ceasefire occurred in 2015. Since 2018, sporadic clashes have occurred due to both sides' lack of disarmament and political guarantees. After the 2021 coup, three attitudes, behaviors, and contradictions have emerged, resulting in daily battles. However, the Karen people are no longer fighting for their liberation, most Burmans are joining the struggle, and federal democracy is becoming clearer. Since the coup was staged to rig the 2020 election, the military has been fighting to suppress the rule of law. The chairman of the Japanese Nippon Foundation and the KNU met on March 10, 2022, to coordinate the 2012 NCA between the conflicting parties (Esther, 2022), but progress has yet to be made. In conclusion, peace and conflict are always in flux, and a compromise is needed to reach a ceasefire. The Myanmar military held similar talks but could not guarantee the outcome, the coup disrupted the peace process, and armed conflict peaked after 2021. Keywords: Armed Conflict in Karen State,2021 Military Coup, Karen Conflicting Party, Karen Conflict analysis,Peace and conflict